2019
DOI: 10.1002/ana.25625
|View full text |Cite
|
Sign up to set email alerts
|

The “maternal effect” on epilepsy risk: Analysis of familial epilepsies and reassessment of prior evidence

Abstract: Objective Previous studies have observed that epilepsy risk is higher among offspring of affected women than offspring of affected men. We tested whether this “maternal effect” was present in familial epilepsies, which are enriched for genetic factors that contribute to epilepsy risk. Methods We assessed evidence of a maternal effect in a cohort of families containing ≥3 persons with epilepsy using 3 methods: (1) “downward‐looking” analysis, comparing the rate of epilepsy in offspring of affected women versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 35 publications
(87 reference statements)
0
8
0
Order By: Relevance
“…The findings from this large population‐based study showed a clear maternal effect in epilepsy, thereby confirming the results of previous population‐based studies. This study also provides the first evidence that the maternal effect may extend to familial epilepsies, but the paradox of the absence of a maternal effect in selected high density families 9 remains unexplained.…”
Section: Resultsmentioning
confidence: 71%
See 4 more Smart Citations
“…The findings from this large population‐based study showed a clear maternal effect in epilepsy, thereby confirming the results of previous population‐based studies. This study also provides the first evidence that the maternal effect may extend to familial epilepsies, but the paradox of the absence of a maternal effect in selected high density families 9 remains unexplained.…”
Section: Resultsmentioning
confidence: 71%
“…In two recent studies of multiplex families, 9,10 there was no evidence of a maternal effect, suggesting that the distribution of causal genetic and non‐genetic factors may differ between sporadic and familial epilepsies. However, these studies were based on highly selected populations.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations